The Impact of Multifocal Intraocular Lens in Retinal Imaging with Optical Coherence Tomography - Dias-Santos, A (2015)
Multifocal intraocular lenses (MF IOLs) have concentric optical zones with different dioptric power, enabling patients to have good visual acuity at multiple focal points. However, several optical limitations have been attributed to this particular design. The purpose of this study is to access the effect of MF IOLs design on the accuracy of retinal optical coherence tomography (OCT). Cross-sectional study conducted at the Refractive Surgery Department of Central Lisbon Hospital Center. Twenty-three eyes of 15 patients with a diffractive MF IOL and 27 eyes of 15 patients with an aspheric monofocal IOL were included in this study. All patients underwent OCT macular scans using Heidelberg Spectralis®. Macular thickness and volume values and image quality (Q factor) were compared between the two groups. There were no statistically significant differences between both groups regarding macular thickness or volume measurements. Retinal OCT image quality was significantly lower in the MF IOL group (p < 0.01). MF IOLs are associated with a significant decrease in OCT image quality. However, this fact does not seem to compromise the accuracy of spectral domain OCT retinal measurements.